The Leukodystrophies HBSL and LBSL—Correlates and Distinctions - Muthiah, Annapoorani; Housley, Gary D.; Klugmann, Matthias; Fröhlich, Dominik (Frontiers in Cellular Neuroscience, 2021)
Aminoacyl-tRNA synthetases (ARSs) accurately charge tRNAs with their respective amino acids. As such, they are vital for the initiation of cytosolic and mitochondrial protein translation. These enzymes have become increasingly scrutinized in recent years for their role in neurodegenerative disorders caused by the mutations of ARS-encoding genes. This review focuses on two such genes – DARS1 and DARS2 - which encode cytosolic and mitochondrial aspartyl-tRNA synthetases, and the clinical conditions associated with mutations of these genes. We also describe attempts made at modelling these conditions in mice, which have both yielded important mechanistic insights. Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) is a disease caused by a range of mutations in the DARS2 gene, initially identified in 2003. Ten years later, hypomyelination with brainstem and spinal cord involvement and leg spasticity (HBSL), caused by mutations of cytosolic DARS1, was discovered. Multiple parallels have been drawn between the two conditions. The Magnetic Resonance Imaging (MRI) patterns are strikingly similar, but still set these two conditions apart from other leukodystrophies. Clinically, both conditions are characterized by lower limb spasticity, often associated with other pyramidal signs. However, perhaps due to earlier detection, a wider range of symptoms, including peripheral neuropathy, as well as visual and hearing changes have been described in LBSL patients. Both HBSL and LBSL are spectrum disorders lacking genotype to phenotype correlation. While the fatal phenotype of Dars1 or Dars2 single gene deletion mouse mutants revealed that the two enzymes lack functional redundancy, further pursuit of disease modeling are required to shed light onto the underlying disease mechanism, and enable examination of experimental treatments, including gene therapies.